IMPACT OF THE AIRFIELD ELECTRICAL SYSTEM ON FLIGHT SAFETY - Z. Shamsiev; B. Suyunov (Web of Journals Publishing, 2025)
This article analyzes the impact of airport electrical systems on flight safety. It examines the role of all electronic systems at airports, including navigation, ground control, communication, and management systems, in ensuring flight safety through efficient operation. Malfunctions or interruptions in electrical systems can pose a threat to aviation safety, making it crucial to ensure their reliability and uninterrupted operation. The article also discusses the requirements for maintenance and monitoring systems of electrical systems at airports, as well as measures necessary to enhance safety protocols. Furthermore, it provides insights into engineering aspects, technological advancements, and new innovative solutions.
Keywords: Airport Electrical Systems, Flight Safety, Reliability of Electrical Systems, Navigation Systems, Ground Control, Communication Systems, Management Systems, Maintenance Services, Aviation Safety, System Malfunctions, Enhancing Safety Measures, Innovative Solutions, Monitoring of Electrical Systems.